From the history of the decision-making of collective farm production in the Fergana Valley agriculture - Kholmatov , Muydin (The Lingua Spectrum, 2025)
This article examines the establishment of collective farm-based (kolhoz) production in the villages of the Fergana Valley as a result of the Soviet government’s policy of mass collectivization and its socio-economic consequences. The forms of labor organization and production within the collective farm system are highlighted.